Reconsidering the management of patients with cancer with viral hepatitis in the era of immunotherapy. Issue 2 (16th October 2020) - Ziogas, Dimitrios C; Kostantinou, Frosso; Cholongitas, Evangelos; Anastasopoulou, Amalia; Diamantopoulos, Panagiotis; Haanen, John; Gogas, Helen
Abstract : In the evolving immune-oncology landscape, numerous patients with cancer are constantly treated with immune checkpoint inhibitors (ICPIs) but among them, only sporadic cases with pre-existing hepatitis B virus (HBV) and hepatitis C virus (HCV) are recorded. Despite the global dissemination of HBV and HCV infections, viral hepatitis-infected patients with cancer were traditionally excluded from ICPIs containing trials and current evidence is particularly limited in case reports, retrospective cohort studies and in few clinical trials on advanced hepatocellular carcinoma. Thus, many concerns still remain about the overall oncological management of this special subpopulation, including questions about the efficacy, toxicity and reactivation risks induced by ICPIs. Here, we examine the natural course of both HBV and HCV in cancer environment, review the latest antiviral guidelines for patients undergoing systematic cancer therapies, estimating treatment-related immunosuppression and relocate immunotherapy in this therapeutic panel. Among the ICPIs-treated cases with prior viral hepatitis, we focus further on those experienced HBV or HCV reactivation and discuss their host, tumor and serological risk factors, their antiviral and immunological management as well as their hepatitis and tumor outcome. Based on a low level of evidence, immunotherapy in these specific cancer cases seems to be associated with no inferior efficacy and with a relevantly low reactivation rate. However, hepatitis reactivation and subsequent irreversible complications appeared to have poor response to deferred antiviral treatment. While, the prophylactic use of modern antiviral drugs could eliminate or diminish up front the viral load in most cases, leading to cure or long-term hepatitis control. Taking together the clinical significance of preventive therapy, the low but existing reactivation risk and the potential immune-related hepatotoxicity, a comprehensive baseline assessment of liver status, including viral hepatitis screening, before the onset of immunotherapy should be suggested as a reasonable and maybe cost-effective strategy but the decision to administer ICPIs and the necessity of prophylaxis should always be weighed at a multidisciplinary level and be individualized in each case, up to be established by future clinical trials.